2020
DOI: 10.34172/jlms.2020.54
|View full text |Cite
|
Sign up to set email alerts
|

Photobiomodulation in Sciatic Nerve Crush Injuries in Rodents: A Systematic Review of the Literature and Perspectives for Clinical Treatment

Abstract: Objective: The aim of the study was to perform a literature review to analyze the effect of photobiomodulation in experimental studies on peripheral nerve regeneration after sciatic nerve crush injury in rodents. Methods: A bibliographic search was performed in the electronic databases, including MEDLINE (PubMed), SCOPUS, and SciELO, from 2008 to 2018. Results: A total of 1912 articles were identified in the search, and only 19 fulfilled all the inclusion criteria. Along with the parameters most found in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…equals 5 Joules/cm 2 [33,34] . This was coinciding with many studies concerned with biostimulation and nerve regeneration that showed optimum results at the power off 0.5W and should not exceed it [35][36][37] .…”
Section: Discussionsupporting
confidence: 76%
“…equals 5 Joules/cm 2 [33,34] . This was coinciding with many studies concerned with biostimulation and nerve regeneration that showed optimum results at the power off 0.5W and should not exceed it [35][36][37] .…”
Section: Discussionsupporting
confidence: 76%
“…The score 2 was observed for only one day. This is not true for the sciatic nerve, where the recovery is observed after 3 weeks [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of PBM therapy have been also widely reported after injury of the sciatic nerve (19,20). Sciatic functional index (SFI) and range of motion (ROM) analyses have revealed an acceleration of functional nerve recovery following PBM treatment (830 nm) at 8 J/cm 2 14 days after surgery (21).…”
Section: Behavioral Effect Of Irmentioning
confidence: 98%